2023
DOI: 10.1111/jpy.13325
|View full text |Cite
|
Sign up to set email alerts
|

The diatom Fragilariopsis cylindrus: A model alga to understand cold‐adapted life

Abstract: Conducting research in polar regions is still a significant challenge because of issues with access and working at subfreezing temperatures. Yet, polar environments are home to significant biological diversity, including diverse primary producers. As photosynthesis on land is limited by permafrost and glaciers, marine phytoplankton groups and, especially, diatoms underpin most of the polar food web (Boyd, 2002;Horner et al., 1992;Smetacek, 1999). Diatoms can cope well with low temperatures and significant seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Phylogenetic analyses indicated that diatoms horizontally acquired FAS1 from bacteria, as there is evidence for at least six instances of horizontal gene transfer within our analysis ( Figure 7D ). Broadly, the FAS1 domain is widely distributed in diatoms, with ~140 marine and freshwater diatoms found to contain this protein domain, including the model cold-adapted diatom Fragilariopsis cylindrus [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analyses indicated that diatoms horizontally acquired FAS1 from bacteria, as there is evidence for at least six instances of horizontal gene transfer within our analysis ( Figure 7D ). Broadly, the FAS1 domain is widely distributed in diatoms, with ~140 marine and freshwater diatoms found to contain this protein domain, including the model cold-adapted diatom Fragilariopsis cylindrus [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…More broadly, our phylogenetic analyses suggest this fasciclin-mediated rafting hypothesis may not be unique to Lake Erie diatoms alone. Fasciclins were identified in ~140 marine and freshwater diatoms, including the model polar marine diatom F. cylindrus [ 69 ]. Hence, this further implies an ecophysiological role exists for these proteins in the globally frigid waters, which in turn indicates that further research is required regarding the role of fasciclins within polar aquatic systems and psychrophilic organisms broadly, especially when considering the rapid global decline in ice cover.…”
Section: Discussionmentioning
confidence: 99%
“…Phaeodactylum tricornutum has proven highly successful in revealing fundamental aspects of diatom biology that are relevant to many species. Diatom research is now greatly benefitting from the establishment of new ecologically relevant model systems (Ferrante et al, 2023;Otte et al, 2023;Poulsen & Kröger, 2023). Without doubt, the fundamental and practical insights gained and still to come through the study of P. tricornutum will support comparative investigations, essential for addressing the significance of diatom diversity in the context of adaptation and evolution.…”
Section: Discussionmentioning
confidence: 99%